PROSPECTS AND TASKS OF KOREAN STUDIES IN KAZAKHSTAN THROUGH ANALYSIS OF COLLABORATIVE AND SUPPORT CASE OF KOREA-KAZAKHSTAN: FOCUSED ON AL-FARABI KAZAKH NATIONAL UNIVERSITY CASE (Journal of Oriental Studies, 2019)
Through the case of the Al- Farabi KazNU and to suggest some solutions of problems, which are obstacles to the development of Ko- rean Studies in Kazakhstan. For this, the author searched the current state of cooperation within financial and material support, academic cooperation, education and cultural activities between Al-Farabi KazNU (Department of the Far East-Korean Studies) and Korea (government, non-governmental organizations and organizations). Specifically, for the purpose of this case analysis, the author provided evidences that demonstrate the supports and cooperation between Al-Farabi KazNU and Korea during the last three and a half years (2015-18). Through this case analysis, the author confirmed that continuous financial and material supports from the Korean side and cooperation in various fields have been contributing to the development of Korean Studies in Kazakhstan.Key words: collaboration and support, Korean Studies in Kazakhstan, Al-Farabi KazNU.